Association between glucose-lowering treatment and cancer metastasis among patients with preexisting type 2 diabetes and incident malignancy - Noh, Yoojin; Jeon, Sang Min; Shin, Sooyoung (International Journal of Cancer, 2019)
Preclinical data suggested that dipeptidyl peptidase-4 (DPP-4) inhibitors may promote metastatic progression of preexisting cancer via nuclear factor erythroid 2-related factor 2 (NRF2) activation. We aimed to investigate the association between different glucose-lowering treatments, including DPP-4 inhibitors and metformin, both with potential NRF2 modulating effects, and new-onset metastatic cancer among type 2 diabetes patients with comorbid incident cancer. This population-based cohort study included 223,530 diabetic patients newly diagnosed with primary cancer during 2009–2011 in Korea. The patients were categorized into five study cohorts in accordance with treatment modalities during the follow-up until the end of 2016: no-antidiabetic drugs (no-AD), metformin, DPP-4 inhibitors, metformin+DPP-4 inhibitors, and insulin treatment. After propensity score (PS) matching in a 1:1 ratio against the no-AD group, 18,805 patients in metformin, 1,865 in DPP-4 inhibitors, 31,074 in metformin+DPP-4 inhibitors, and 1,895 patients in insulin groups were identified for cohort entry and analyzed against the corresponding number of no-AD patients in each PS-matched comparison pair. Metastatic risk was lower with metformin plus or minus DPP-4 inhibitors (HR 0.84, 95% CI 0.79–0.90 and 0.87, 0.80–0.95, respectively), not significantly associated with DPP-4 inhibitors (0.99, 0.77–1.29) except after thyroid cancer (3.89, 1.01–9.64), and higher with insulin therapy (1.81, 1.46–2.24) compared to no-AD use for all cancers combined. In conclusion, DPP-4 inhibitor therapy was not associated with significant risk of cancer metastasis relative to no-AD therapy, irrespective of patient age and sex, except after thyroid cancer, while metastatic risk was decreased with metformin treatment among type 2 diabetes patients with preexisting cancer.
Keywords: Adult; Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Diabetes Mellitus, Type 2; Dipeptidyl-Peptidase IV Inhibitors; Female; Humans; Hypoglycemic Agents; Insulin; Male; Metformin; Middle Aged; Neoplasm Metastasis; Propensity Score; Republic of Korea; Thyroid Neoplasms; Young Adult; antidiabetic drug; cancer; dipeptidyl peptidase-4 inhibitor; metastasis; type 2 diabetes